2016
DOI: 10.1080/00343404.2016.1242718
|View full text |Cite
|
Sign up to set email alerts
|

R&D collaborations and the role of proximity

Abstract: R&D collaborations and the role of proximity. Regional Studies. This paper explores the impact of proximity measures on knowledge exchange measured by granted research and development (R&D) collaboration projects in German NUTS-3 regions. The results are obtained from a spatial interaction model including eigenvector spatial filters. Not only geographical but also other forms of proximity (technological, organizational and institutional) have a significant influence on the emergence of collaborations. Furtherm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 32 publications
3
23
0
Order By: Relevance
“…The conducted analyses confirm that geographic location proves to be the substantial differentiating factor for rural boroughs. We found that such rural boroughs perform better than peripheral rural boroughs from the demographic, business and infrastructure perspective, which confirms the deconcentration hypothesis for Poland, similarly to the studies for other countries presented in [Renkow, Hoover 2000;McArthur et al 2010;Partridge et al 2010;Marek et al 2017]. The deconcentration hypothesis works for Poland for a 40 km distance between the centres of the two administration entities, which translates into a 20-60 km distance to the provincial capital for the RB's inhabitants.…”
Section: Discussionsupporting
confidence: 87%
“…The conducted analyses confirm that geographic location proves to be the substantial differentiating factor for rural boroughs. We found that such rural boroughs perform better than peripheral rural boroughs from the demographic, business and infrastructure perspective, which confirms the deconcentration hypothesis for Poland, similarly to the studies for other countries presented in [Renkow, Hoover 2000;McArthur et al 2010;Partridge et al 2010;Marek et al 2017]. The deconcentration hypothesis works for Poland for a 40 km distance between the centres of the two administration entities, which translates into a 20-60 km distance to the provincial capital for the RB's inhabitants.…”
Section: Discussionsupporting
confidence: 87%
“…The key city output has a positive sign, which demonstrates that key cities are promoting external technology flows. The coefficient of geographical distance is negative and significant at p < 0.001 in Models 3-6, further indicating that, owing to spatial proximity, intercity technology transfer tends to diffuse to cities with close distances, confirming the neighborhood diffusion effect of technology transfer within urban agglomerations [24,27]. The effect of industrial structure similarity is non-significant in Models 5 and 6, which might be because competition will inhibit the transfer of patents if the industrial structure between cities is very similar.…”
Section: Potential Determinants Of the Strength Of Intercity Patent Tmentioning
confidence: 83%
“…Ma et al (2014) found that the impact of geographical proximity on scientific cooperation became stronger with the development of information technology in China [25]. Cognitive, organizational, and social proximity have also been studied by scholars [26,27]. Moreover, urban, industrial, and technological gaps, as well as innovation capacity, are also considered to affect innovation linkages [28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…Folta (2011) andHervas-Oliver, Sempere-Ripoll, Rojas Alvarado, andEstelles-Miguel (2018) show that firms' innovative performance or general performance is attributable mainly to positive externalities generated by localization in agglomerations or business clusters. Marek, Titze, Fuhrmeister, and Blum (2017) obtained statistically significant models for German NUTS-3 regions, which show a decreasing relationship between geographical distance and research and development (R&D) collaboration. The threshold value for the geographical distance amounted to 50 km.…”
Section: Introductionmentioning
confidence: 99%